Commo. Russell Ihrig, Superintendent of Academy, Issues Statement on State Budget Hearing School - Vallejo Times-Herald (Vallejo Times-Herald)
Commo. Russell M. Ihrig, USN (ret.), superintendent of the, California Maritime Academy, issued a statement yesterday for presentation to the Assembly Ways and Means Committee. The committee will hold a hearing on the proposed elimination of the academy and reach a recommendation on the future of the school. The committee's subcommittee on education last week voted eight to three to abolish the academy and transfer its students to another state school.